Observation of directed low of hypernuclei 3ΛH and 4ΛH in √𝑠NN=3 GeV Au+Au collisions at RHIC - Aboona, Bassam; Deppner, Ingo Martin; Leung, Yue; Söhngen, Yannick; Weidenkaff, Philipp (Physical review letters, 2023)
We report here the first observation of directed flow ($v_1$) of the hypernuclei $^3_{Λ and $^4_{Λ in mid-central Au+Au collisions at $\sqrt{s_{\rm NN}}$ = 3 GeV at RHIC. These data are taken as part of the beam energy scan program carried out by the STAR experiment. From 165 $×$ 10$^{6}$ events in 5%-40% centrality, about 8400 $^3_{Λ and 5200 $^4_{Λ candidates are reconstructed through two- and three-body decay channels. We observe that these hypernuclei exhibit significant directed flow. Comparing to that of light nuclei, it is found that the midrapidity $v_1$ slopes of $^3_{Λ and $^4_{Λ follow baryon number scaling, implying that the coalescence is the dominant mechanism for these hypernuclei production in such collisions.
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, NN ist dabei tiefgestellt; 3 und 4 sind hochgestellt, Lambda ist jeweils tiefgestellt, 3 und 4 stehen jeweils über dem Lambda
*STAR Collaboration: I.M. Deppner, Y.H. Leung, Y. Söhngen, P.C. Weidenkaff [und 347 weitere Personen]
Gesehen am 03.07.2024